Pengaruh Tingkat Pendidikan, Pelatihan, dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Desa Berbasis SISKEUDES - Setiadi, I Nyoman Dedi; Devi, Sunitha (Jurnal Akuntansi Profesi, 2020)
This research aimed to determine empirical evidence about the effect of the level of education, training and internal control systems on the quality of financial reports based on Siskeudes. This is a quantitative research with primary data which collected from questionnaires and measured using likert scale. The populations is the Siskeudes Operators with a total population of 133 people. The sampling technique uses Isaac table so as to get a sample of 88 people. Data analysis technique used is multiple linear regression analysis using IMB SPSS ver. 24.0. The results of this research indicate that Education level, training and internal control systems affected positively towarded the quality of village financial reports based on Siskeudes.